Arah dan fungsi pendidikan islam - Zahiroh, Zakiyatuz (Maliki Interdisciplinary Journal, 2025)
The direction and function of education are very influential. Without these two components, education willn’t reach its desired goal. It can even deviate and not be in accordance with the concept of education. In this journal, I discuss the direction and function of Islamic education. Globally, Islamic education is education that is in accordance with Islamic teachings. And of course, the presence or absence of these two components will have an impact on the learning process and outcomes for students. For that, I want to share knowledge about the application and integrity of Islamic values ​​in the world of education. In order to create an intellectual generation not only in the academic field, but also on the religious side. Of course, in accordance with the development of the times.